Neuroprotective treatment options for neonatal hypoxic-ischemic encephalopathy: Therapeutic hypothermia and beyond - Merih Cetinkaya (Elsevier, 2024)
Hypoxic-ischemic encephalopathy (HIE) is the most common form of neonatal encephalopathy that develops due to perinatal asphyxia or ischemia in term and late-preterm infants. It is an important cause of significant neurological impairment and also mortality in newborns worldwide. The pathophysiology of HIE is multifactorial and involves complex cascades of cellular and biochemical events in the brain including excitotoxicity, oxidative stress, inflammation, and cell death, respectively. Therapeutic hypothermia (TH), is the only standard neuroprotective therapy for HIE and is associated with reduced composite outcome of death or major neurodevelopmental disability. However, although TH is beneficial, neonates with HIE still experience unacceptably high rate of devistating morbidities. Therefore, research for adjunctive therapies continue to further improve outcomes in infants with HIE. In this review, both TH and other promising adjunctive neuroprotective therapies are discussed for developing future treatment strategies.